An ESIPT-based fluorescent probe for the detection of multiple analytes and a facile approach to discriminate between arsenate and pyrophosphate in water. Issue 6 (27th September 2022) - Gadiyaram, Srushti; Ghule, Vikas D.; Ghosh, Amrita; Jose, D. Amilan
Abstract : A simple ESIPT-based fluorescent probe for the detection of the multiple analytes such as chromium (Cr 3+ ), arsenate (HAsO4 2− ), and pyrophosphate (PPi, P2 O7 4− ) has been reported. Abstract : A simple ESIPT-based fluorescent probe for the detection of the multiple analytes such as chromium (Cr 3+ ), arsenate (HAsO4 2− ), and pyrophosphate (PPi, P2 O7 4− ) has been reported. The probe HJ-DNP displayed weak emission in organic solvents owing to excited-state intramolecular proton transfer (ESIPT) and –CN isomerization. However, upon the addition of water, the fluorescence emission could be increased to a maximum through the aggregation-induced emission (AIE) behavior of HJ-DNP . The combined effects of ESIPT and AIE in the DMSO–water mixture were used to sense multiple analytes. The probe HJ-DNP could selectively detect Cr 3+ through the CHEF mechanism with a turn-on fluorescence response. The limit of detection (LOD) for Cr 3+ ions was estimated to be as low as 3.9 μM. The probe HJ-DNP was also used to detect Cr 3+ ions in tomato extract. The probe HJ-DNP also binds preferentially with arsenate and pyrophosphate (PPi) in the presence of various anions. The sensing of arsenate and PPi could be carried out through naked-eye detection with a color change from orange to red; the LOD values are calculated to be 3.9 μM and 0.19 mM for arsenate and PPi, respectively. It was found that arsenate detection is more sensitive than PPi detection. Moreover, the different emission behavior of HJ-DNP in the presence of arsenate or PPi was used to easily discriminate them. The probe HJ-DNP was used to detect arsenate in real water samples. Arsenate was also detected and adsorbed from water samples using HJ-DNP incorporating alginate polymer beads.